Impact of Institutional Agricultural Credit on Agricultural Production A Case Study in the Vavuniya District - Umashankar, K.; Sivarajasingam, S.; Jogaratnam, T. (Jaffna Science Association, 2000)
Credit is thought to be a strategic variable in enhancing agricultural production in developing countries. Therefore government in these countries place special importance on the provision of institutional credit in agriculture. This study was carried out to assess the implication of institutional credit on the red onion production in Vavuniya divisional secretariat division, which is typical of the Sri Lankan dry zone. Purpose randomly selected sample farmers, from the Kovilkulam and Pamparnadu agrarian service centre divisions were interviewed with a structured questionnaire. The study compared the calculated t-probability values with fixed probability level of 0.05. An appropriate functional form was decided by comparing the t- probability values, R. square, adjusted R square, D. W and VIF (Variation Inflation Factors) of the functions. Firstly t-test was performed to compare the yield difference of red onion both borrowers and non-borrowers. Second t-test was performed to test the total liability difference of both borrowers and non-borrowers. Here total liability implies the summation of formal and informal borrowings of borrowers and total informal borrowings of non-borrowers. Then multiple regression analysis was performed to test the influence of total borrowing on the level of inputs used by the farmers. Second multiple regression analysis was done to test the production response to the input usage level of borrowers and non-borrowers. Finally correlation analysis was performed to check for any interrelationship within the inputs used in the production. 0.0001 t-probability value implies that there is a significant difference found between the yield level of the borrowers and non- borrowers. According to the results of the second t-test, the t probability value 0.0078 indicates the significant difference found between the total liabilities of both category farmers. Total borrowing of borrowers had a significant impact on the input usage level of land, seed hired labour and nitrogen fertilizer. But for non-borrowers total borrowing were found to be significant only for the inputs of seed and hired labour. Final regression analysis implies the productivity of purchased inputs on the production. But the productivity of inputs was found to be higher for the borrowers of credit than non-borrowers. Interactions found within two inputs of non-borrowers were detected by the correlation analysis. Ultimately the research concludes that institutional credit has statistically significant impact on the production of red onion.